Giustizia e diritti - Tafaro, Sebastiano (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The proclamation of rights without contextual means to ensure. is not an effective source of justice and leads to a justice crisis. A new ‘model’ must be proposed , which sees the Roman law and process as a source of innovative suggestions and ideas that apply to the present. In particular, it is important to emphasize the ‘Treaties’ as threatening to man and the environment. The Roman law indicates the way to prevent the underlying economic and financial reign of the few.